Machiavellianism and Adult Attachment in General Interpersonal Relationships and Close Relationships - Ináncsi, Tamás (Eur J Psychol, 2015)
Up to the present, the relationship between Machiavellianism and adult attachment has remained a question to be answered in the psychological literature. That is why this study focused on the relationship between Machiavellianism and attachment towards significant others in general interpersonal relationships and in intimate-close relationships. Two attachment tests (Relationship Questionnaire and long-form of Experiences in Close Relationship) and the Mach-IV test were conducted on a sample consisting of 185 subjects. Results have revealed that Machiavellian subjects show a dismissing-avoidant attachment style in their general interpersonal relationships, while avoidance is further accompanied by some characteristics of attachment anxiety in their intimate-close relationships. Our findings further refine the relationship between Machiavellianism and dismissing-avoidant attachment. Machiavellian individuals not only have a negative representation of significant others, but they also tend to seek symbiotic closeness in order to exploit their partners. This ambitendency in distance regulation might be particularly important in understanding the vulnerability of Machiavellian individuals.